Making, unmaking, remaking: Mapping the boundaries of professional legitimacy, identity and practice in probation in England and Wales - Tidmarsh, Matt (Criminology & criminal justice, 2024)
This article maps the (shifting) boundaries of professional legitimacy, identity and practice in probation in England and Wales. Probation established itself in the 20th century as a core institution in the modernist pursuit of offender rehabilitation; however, changing political economic priorities in recent decades have prompted a new consensus that also incorporates mentalities of punitivism, managerialism and risk. With a particular emphasis on the reunification of services after the Transforming Rehabilitation reforms, the article presents a practical and moral case for how the Government’s (re)professionalisation agenda can be developed. It draws upon the sociology of the professions literature to emphasise the service’s ‘interstitiality’ as a professional jurisdiction that operates between different social spheres. The article argues that reunification provides an opportunity to remake the boundaries of professional practice in such a way that people on probation can take ownership of their desistance, while reasserting the service’s internal self-image and external legitimacy.